Correlation Between Liver Volume, Portal Vascular Anatomy, and Hepatic Perfusion in Dogs With Congenital Portosystemic Shunt Before and After Placement of Ameroid Constrictors. Issue 8 (12th April 2014) - Zwingenberger, Allison L.; Daniel, Leticia; Steffey, Michele A.; Mayhew, Philipp D.; Mayhew, Kelli N.; Culp, William T. N.; Hunt, Geraldine B.
<x xml:space="preserve">Abstract</x> Objective To correlate changes in hepatic volume, hepatic perfusion, and vascular anatomy of dogs with congenital extrahepatic portosystemic shunts, before and after attenuation with an ameroid constrictor. Study Design Prospective study. Animals Dogs (n = 22) with congenital extrahepatic portosystemic shunts. Methods CT angiography and perfusion scans were performed before and after attenuation of a portosystemic shunt with an ameroid constrictor. Changes in hepatic volume, hepatic perfusion, and vascular anatomy were measured. Portal scintigraphy was performed in 8 dogs preoperatively and 22 dogs postoperatively. Results Dogs with smaller preoperative liver volumes had greater increases in liver volume postoperatively compared with those with larger preoperative liver volumes. Hepatic arterial fraction was increased in dogs preoperatively and returned to normal range after shunt attenuation, and was correlated with increase in liver size and decreased shunt fraction. Three dogs with no visible portal vasculature preoperatively developed portal branches postoperatively. Conclusions Dogs with smaller preoperative liver volumes had the largest postoperative increase in liver volume. Hepatic arterial perfusion and portal scintigraphy correlate with liver volume and are indicators of successful shunt attenuation. Dogs without visible vasculature on CT angiography had visible portal vasculature postoperatively.